PENYULUHAN BAHAYA POLUSI UDARA PADA MASYARAKAT DI KELURAHAN RAWA BUAYA JAKARTA BARAT - Khairani, Rita; Hastuty, Dewi (Universitas Trisakti, 2024)
DKI Jakarta as the capital city of Indonesia is a center of various activities and higher population density than other provinces. The transportation sector is the largest contributor to air pollution from motor vehicles. In the World Air Quality Report 2023, Jakarta ranks seventh for the world's most polluted cities. Long-term exposure to air pollution will be the beginning of various diseases, such as respiratory disease, heart disease, stroke, congenital diseases, and malignancy. Air pollution is the invisible cause of death of 29% of lung cancer deaths, and 25% of heart disease deaths. The need for a good understanding of the impact of air pollution on respiratory health is the background of health service activity. This activity was held on Saturday, November 4th, 2023 at GKI Pakis Raya, Rawa Buaya subdistrict, West Jakarta, attended by 104 local residents who were dominated by women (87%) with an average age of 47 years. The activity method is carried out by completing a pre-test, counseling with presenting the material, question and answer discussion and ending with a post-test. The results obtained through this activity were an increase in participants' knowledge about the impact of air pollution on breathing and health as evidenced by an increase in the average post test score of 38.9%. from the previous 53.38 to 79.4. In conclusion, the activity had a positive effect on increasing respondents' knowledge about the impacts of air pollution. The suggestion is by carrying out regular evaluations of behavioral changes after receiving counseling